2004
DOI: 10.1111/j.0022-2445.2004.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of cohabitation in family formation: The United States in comparative perspective

Abstract: The prevalence of nonmarital cohabitation is steadily increasing in the United States. In evaluating the contribution of this new living arrangement to family formation, analysts have relied primarily on comparisons between individuals who cohabit and those who do not. We complement this line of inquiry by comparing the United States and 16 industrialized nations. We first identify six conceptually distinct ideal types of cohabitation with respect to family formation. We then propose empirical indicators to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
456
5
23

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(500 citation statements)
references
References 29 publications
16
456
5
23
Order By: Relevance
“…We included both cohabiting and married couples in our analyses. The incidence of cohabitation is Germany high, the duration is short, and a high percentage of cohabiting unions end in marriage (Heuveline & Timberlake, 2004). Prior research in the United States has suggested that the association between economic factors and relationship quality does not vary by relationship type (Hardie & Lucas, 2010).…”
Section: The Current Studymentioning
confidence: 99%
“…We included both cohabiting and married couples in our analyses. The incidence of cohabitation is Germany high, the duration is short, and a high percentage of cohabiting unions end in marriage (Heuveline & Timberlake, 2004). Prior research in the United States has suggested that the association between economic factors and relationship quality does not vary by relationship type (Hardie & Lucas, 2010).…”
Section: The Current Studymentioning
confidence: 99%
“…En somme, à l'instar d'autres sociétés (Heuveline et Timberlake, 2004), l'union libre et le mariage au Québec semblent désormais très similaires. Dans ce contexte, si l'hypothèse de la sélec-tion est juste, on devrait pouvoir trouver un modèle permettant de prédire la mise en commun des revenus qui est aussi performant qu'un modèle incluant l'état matrimonial comme valeur explicative.…”
Section: La Diversité Des Couples En Union Libre Au Québecunclassified
“…Once marriage was no longer the only context for childbearing and unmarried cohabiting couples increasingly had children (Sobotka and Toulemon 2008) -because of changing norms and values that broke the traditional link between marriage and childbearing (Billari 2001) -unmarried cohabitation became an alternative to marriage (Manning 1993;Smock 2000;Raley 2001;Kiernan 2004). Several classifications of unmarried cohabitation offer an insight into how this type of relationship has evolved over time, from a prelude to marriage to an alternative (Heuveline and Timberlake 2004;Perrelli-Harris et al 2009;Hiekel, Liefbroer, and Poortman 2012). The speed of this evolution differs between European regions.…”
Section: Theory and Hypothesesmentioning
confidence: 99%